107k views
10 votes
Find y

Solve the simultaneous
equations


3x + 2y = 27 3x - Y = 9


User Weier
by
5.8k points

1 Answer

4 votes

Answer:


y = 6

Explanation:

To find
y, we need to eliminate
x in this system of equations:


3\cdot x + 2\cdot y = 27 (1)


3\cdot x - y = 9 (2)

From (1) and (2):


x = (27-2\cdot y)/(3)


x = (9+y)/(3)

Then, we equalize both expressions and solve for
y:


(27-2\cdot y)/(3) = (9+y)/(3)


27-2\cdot y = 9 + y


3\cdot y = 18


y = 6

User Will Custode
by
5.7k points